2009
DOI: 10.2174/156720509790147070
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Deposition and Inflammation in APPswe/PS1dE9 Mouse Model of Alzheimers Disease

Abstract: Alzheimer's disease (AD) is characterized by amyloid plaques and neurofibrillary tangles associated with chronic inflammation. APPswe/PS1dE9 is an AD mouse model bearing mutant transgenes of amyloid precursor protein and presenilin-1. Amyloid deposition is present in this mouse model at early stage of life. However, the progression of inflammation and its relationship with amyloid deposition have not been characterized. Here we showed that amyloid plaques were present at 4 months of age and increased with age.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
68
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(78 citation statements)
references
References 69 publications
7
68
1
1
Order By: Relevance
“…The monitoring of inflammation in APPswePS1dE9 versus WT mice at 3, 6 and 12 months of age showed that APPswePS1dE9 mice displayed cytokine production, in particular IL-1β in cortex at 12 months of age and hippocampus from 6 months, but TNF-α levels increased only in hippocampus at 12 months and were less than 10 pg/mg protein as previously described [37,38]. In line with our work, Jin et al .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The monitoring of inflammation in APPswePS1dE9 versus WT mice at 3, 6 and 12 months of age showed that APPswePS1dE9 mice displayed cytokine production, in particular IL-1β in cortex at 12 months of age and hippocampus from 6 months, but TNF-α levels increased only in hippocampus at 12 months and were less than 10 pg/mg protein as previously described [37,38]. In line with our work, Jin et al .…”
Section: Discussionsupporting
confidence: 92%
“…Recently, we showed, in primary cultures of neurons, astrocytes and microglia, that IL-1β induced autophagy with accumulation of many acidic vesicles loaded with autophagic markers (p62 and LC3) in microglia, whereas Aβ42 prevented the effects of exogenous IL-1β in the production of inflammatory factors and in autophagy impairment [53]. In this present study, we wanted to explore correlations between autophagy and inflammation in vivo by using APPswePS1dE9 mice which displayed amyloid plaques and an inflammatory response at an early stage of the life and progressively increase with age [37,38]. However, their longitudinal status of autophagy has never been studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established that CD11b microglia cell clusters were observed as early as 4 months of age [87]. Other studies established that particularly the microglia cells proliferate around A β plaques, without astrocyte proliferation in these animals; indeed, age-related increases in proliferation in this mouse model were due to increases in newborn BrdU+ cells coexpressing markers for activated microglia [30].…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, we Although Ruan et al (2009) Follow-up measurements in our study were performed 5 and 10 weeks after the baseline study and were combined with the idea that microglial activation could be modulated by a PPAR-γ agonist. PPAR-γ is a nuclear receptor that plays an important role in inflammatory processes.…”
Section: Supplementary Discussionmentioning
confidence: 99%